2022
DOI: 10.3390/app12041798
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Estimation by Photoplethysmogram Decomposition into Hyperbolic Secant Waves

Abstract: Photoplethysmographic (PPG) pulses contain information about cardiovascular parameters. In particular, blood pressure can be estimated using PPG pulse decomposition analysis, which assumes that a PPG pulse is composed of the original heart ejection blood wave and its reflections in arterial branchings. Among pulse decomposition wave functions that have been studied in the literature, Gaussian waves are the most successful ones. However, a more adequate pulse decomposition function could be found to improve blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“… is typically observed during systole, therefore reflects the systolic component. represents the dicrotic wave 10 . represents the additional minor reflections and re-reflections in the systemic vascular structure with lower amplitude than the two main reflected waves 54 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… is typically observed during systole, therefore reflects the systolic component. represents the dicrotic wave 10 . represents the additional minor reflections and re-reflections in the systemic vascular structure with lower amplitude than the two main reflected waves 54 .…”
Section: Methodsmentioning
confidence: 99%
“…where |z i | is the number of features in z i . As most models cannot handle missing data, SHAP values are computed by replacing f (•) in equation (10) with f x (•) , a conditional expectation function of the original model. This step equates to replacing each missing feature with a random value representative of the datapoints the original model was trained over.…”
Section: Shap Values Feature Ranking Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 69 ] investigated the propagation of pulses through an elastic tube filled with viscous fluid under initial pressure using Navier–Stokes equations. In addition, the authors of [ 185 ] proposed pulse decomposition analysis using hyperbolic secant (sech) waves and suggested that hyperbolic secant wave decomposition gives more accurate blood pressure values than the Gaussian function.…”
Section: Contact-based Bp Measurement From Ppg Signalsmentioning
confidence: 99%
“…The photoplethysmography (PPG) waveform is defined by the primary pulse wave resulting from the heartbeat, as well as reflected waves occurring during the pulse propagation 1 . Pulse decomposition analysis (PDA) aims to define these constituent waves, as their parameters are influenced by levels of central systolic BP 2 .…”
Section: Introductionmentioning
confidence: 99%